ChemInform Abstract: Direct Synthesis of Butadiynyl‐Substituted Pyrroles under Solvent‐ and Transition Metal‐Free Conditions. Issue 2 (23rd December 2015) - Tomilin, Denis N.; Pigulski, Bartlomiej; Gulia, Nurbey; Arendt, Agata; Sobenina, Lyubov N.; Mikhaleva, Al'bina I.; Szafert, Slawomir; Trofimov, Boris A.
Abstract: Various title compounds are obtained by highly efficient C—H butadiynylation of substituted pyrroles with halobutadiynes through simple grinding.